Simulation-based Fuzzy Multiple Attribute Decision Making framework for an optimal apron layout for aRoll-on/Roll-off/Passenger terminal considering passenger service quality. (July 2021) - Guolei, Tang; Xiaoyi, Zhao; Zhuoyao, Zhao; Jingjing, Yu; Lei, Guo; Yuhan, Wang
The apron of the Roll-on/Roll-off/Passenger (Ro-Pax) terminal is an accident-prone zone with high risk of traffic congestion and vehicle exhaust pollution in the peak season, which brings a bad experience to passengers and even endangers passengers' health. This study aims to improve the passenger service quality in the peak season by rezoning the Ro-Pax terminal apron and its traffic organization. Thus, we establish a simulation-based Fuzzy Multiple Attribute Decision Making framework to evaluate the passenger service quality and distinguish an optimal layout of the terminal apron. This framework introduces three evaluation indicators (safety, convenience, and comfort and health) and 11 performance indexes to define the passenger service quality, and the values of these indexes are derived from an agent-based simulation model for the Ro-Pax terminal apron operation. Finally, an example of the proposed framework is presented in a case study to show how to select an improved layout of the Ro-Pax terminal apron considering passenger service quality. The result confirms the proposed framework is an effective tool to solve rezoning the Ro-Pax terminal apron and the proposed methodology can also be used to cope with similar problems.